Photoinduced changes of the optical parameters of thin films from Ge 30.8As5.7S63.5 glass - Yakuphanoğlu, Fahrettin; Arsova, D.; Vateva, E. (National Institute of Optoelectronics, 2007)
Extremely high irreversible changes of the optical parameters have been found after long time illumination of thin films thermally evaporated from Ge2As3-AsS3 glass, which belongs to the Ge 2As3-AsS3 line. Illumination of virgin films leads to a blue shift of the absorption edge, photo-bleaching (PB). Changes of the optical band gap, Eg up to about 600 meV (?27%), of the refractive index, n up to 0.2 (?9.5%), as well as the thickness increase ?70 nm (11%) have been obtained. The dependences of the parameters of the irreversible PB on the film thickness (between 0.4 - 1.4 ?m) and the time of illumination (up to 3h) have been investigated. The magnitude of the irreversible PB is compared with that of the irreversible thermo-bleaching after annealing near to the glass transition temperature, as well as with that of the reversible photo-darkening of the annealed films. The reasons for the appearance of such high photo-induced changes, which are interesting for practical uses, are discussed.
Keywords: Chalcogenide films; Optical band gap; Refractive index